Handbook of knowledge representation - Van Harmelen, Frank; Lifschitz, Vladimir; Porter, Bruce, 1956- (Amsterdam ; Boston : Elsevier, 2008)
Knowledge Representation, which lies at the core of Artificial Intelligence, is concerned with encoding knowledge on computers to enable systems to reason automatically. The Handbook of Knowledge Representation is an up-to-date review of twenty-five key topics in knowledge representation, written by the leaders of each field. This book is an essential resource for students, researchers and practitioners in all areas of Artificial Intelligence. * Make your computer smarter * Handle qualitative and uncertain information * Improve computational tractability to solve your problems easily.
Knowledge representation and classical logic / Vladimir Lifschitz, Leora Morgenstern, and David Plaisted -- Satisfiability solvers / Carla P. Gomes ... [et al.] -- Description logics / Franz Baader, Ian Horrocks, Ulrike Sattler -- Constraint programming / Francesca Rossi, Peter van Beek, Toby Walsh -- Conceptual graphs / John F. Sowa -- Nonmonotonic reasoning / Gerhard Brewka, Ilkka Niemelθa, Mirosław Truszczyβnski -- Answer sets / Michael Gelfond -- Belief revision / Pavlos Peppas -- Qualitative modeling / Kenneth D. Forbus -- Model-based problem solving / Peter Struss -- Bayesian networks / A. Darwiche -- Temporal representation and reasoning / Michael Fisher -- Qualitative spatial representation and reasoning / Anthony G. Cohn and Jochen Renz -- Physical reasoning / Ernest Davis -- Reasoning about knowledge and belief / Yoram Moses -- Situation calculus / Fangzhen Lin -- Event calculus / Erik T. Mueller -- Temporal action logics / Patrick Doherty and Jonas Kvarnstrθom -- Nonmonotonic causal logic / H. Turner -- Knowledge representation and question answering / Marcello Balduccini, Chitta Baral, Yuliya Lierler -- The semantic web : webizing knowledge representation / Jim Hendler and Frank van Harmelen -- Automated planning / Alessandro Cimatti, Marco Pistore, Paolo Traverso -- Cognitive robotics / Hector Levesque and Gerhard Lakemeyer -- Multi-agent systems / Wiebe van der Hoek and Michael Wooldridge -- Knowledge engineering / Guus Schreiber.
Includes bibliographical references and indexes.
Keywords: Knowledge Representation (Information Theory).; Electronic books; Electronic books